Clean Energy for Better Environment - Aydinalp, Cumhur (IntechOpen, 2012)
The prospect of producing clean, sustainable power from renewable energy sources is becoming a very important subject, stimulated by recent technological developments that have improved the cost-effectiveness of many renewables and by the increasing concern for the environmental impact and sustainability of conventional fossil and nuclear fuels. This book provides a comprehensive overview of the principal renewable energy sources with a wide range of case studies for each source. It explains the underlying physical and technological principles, and examines the environmental impact of renewable sources and their future prospects. The overall approach is interdisciplinary, covering the economic, social, environmental and policy issues from the point of research on renewable energy. It also tackles the physical and engineering aspects. The book will, therefore, strongly appeal to non-specialist readers who wish to improve their understanding of this complex, fascinating and increasingly important subject.